Pengaruh Model Pembelajaran Jigsaw Terhadap Peningkatan Kemampuan Dribble Bola Basket - Nelce Naa, Febelina; Anwar, Saiful; Istiyono (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This research uses quantitative methods with a descriptive approach. The sample used in this research was 20 students. Data collection techniques in this research are observation, interviews, assessments, assessment of basic basketball dribbling technique abilities, literature study and documentation. The results of this research show that it was found that the average student learning outcomes increased from 61.2 in the initial test to 71.2 in the final test, with an average increase of 10 points. Hypothesis testing shows that there is a significant influence of the jigsaw learning model on improving basketball dribbling ability, with a significance value of 0.000 which is smaller than 0.05. The percentage increase in students' abilities was 16.34%. The learning results obtained showed that the majority of students experienced significant improvement, with the highest increase reaching 40.48 points. However, there are also some students who do not experience improvement. This increase was caused by the jigsaw learning method which involved group discussions, gave students the opportunity to give correct answers, and encouraged a spirit of cooperation, thus making the learning process more interesting and less boring.